IMPACT OF NITROGEN AND SULFUR APPLICATION ON GROWTH AND YIELD OF MAIZE (ZEA MAYS L.) CROP - Rasheed, Muhammad; Ali, Hakoomat; Mahmood, Tariq (Journal of Research (Science), 2004)
The experiment was laid out in randomized complete block design (RCBD) having three replications with net plot of 4.2 x 7.5 m to evaluate the effect of nitrogen and sulfur on growth, yield and quality of double cross hybrid (DCH) maize (Cargil-707). Application of fertilizers at the rate of 150 + 30 and 150 + 20 kg of nitrogen and sulfur per hectare respectively greatly increased dry weight per plant (DWP), plant grains number per ear (GNE) and grain weight per ear (GWE) over other treatments. Similarly, the highest grain yield of 8.59 tons per hectare was recorded from the plot fertilized at the rate of 150 kg N and 30 kg S per hectare, while maximum grain oil content (GOC) and grain protein contents (GPC) were recorded from plot fertilized at the rate of 150 + 30 and 150 + 20 kg N and S per hectare respectively.